Thermal behavior and surface morphology studies on polystyrene grafted sago starch - Janarthanan, Pushpamalar; Wan Yunus, Wan Md. Zin; Ahmad, Mansor (Wiley, 2003)
Polystyrene grafting onto sago starch was carried out by using ceric ammonium nitrate as a redox initiator. The grafted copolymers were characterized by FTIR, thermogravimetry (TGA), differential scanning calorimetry (DSC), and scanning electron microscopy (SEM). FTIR spectra analysis of the grafted chain and commercial polystyrene was identical, indicating that styrene was successfully grafted onto sago starch. TGA thermograms and analysis of DSC curves showed that the thermal stability of starch increases as a result of grafting. SEM micrographs showed the deformed prolate ellipsoidal shape of sago starch particles and this shape disappeared in polystyrene grafted sago starch being replaced with a spongy surface with pores.